Um controle ótimo aplicado a fontes ininterruptas de energia: projeto, validação experimental e análise de desempenho - Ribas, Samuel Polato (2011)
This work presents as contributions a design procedure for controllers applied to single-phase uninterruptible power supplies and the certification of the closed-loop stability and performance using linear matrix inequalities. The design procedure takes into account the IEC62040-3 standard to select the components of an internal model principle based controller that guarantees tracking of sinusoidal reference and rejection of disturbances from typical nonlinear loads. It also takes into account the suitability of the controller for implementation in fixed point digital signal processors, including constraints on data representation and transport delay. A discrete linear quadratic regulator is used to ensure to the closed-loop system satisfactory transient responses and steady-state performance. The proposed design procedure is applied to a prototype of the output stage of an uninterruptible power supply, with simulation and experimental results that totally comply with the requirements of the IEC62040-3 standard. Finally, the performance of closed-loop system is certified by means of linear matrix inequalities that allow to determine the capacity of rejection of disturbances under time-varying or time invariant parametric uncertainties, providing new information on limits of performance for this class of systems.